Nutritional Value of Seaweed to Ruminants - Applegate, Roger D.; Gray, Patrick B. (Rangifer, 1995)
We compared the nutritional quality (apparent digestible dry matter (ADDM), crude protein, total phenolics, gross energy), of 3 seaweed species (Alaria esculenta, Ascophyllum nodosum, Fucus vesiculosis) to that of 3 woody browse species{Acer rubrum, Thuja occidentalis, Abies balsamea), lichen (Usnea spp.), and winter rye (Secale cereals) for ruminants. The ADDM's of the 3 seaweeds (63-80% DM) were 11-167% DM higher and crude protein contents (12.1-14.6% DM) were 68-186% DM higher than the 3 browse species. Seaweeds had lower total phenolics (5.5-10.3% DM) and gross energy (12-15 KJ/g DM), and moderate digestible energy (DE) contents (9-10 KJ/g DM) compared to the browse species. The 3 browse species had ADDM's of 30-57% DM, crude protein contents of 5.1-7.2% DM, total phenolic concentrations of 11.6-16.4% DM, and DE contents of 6-12 KJ/g DM. Winter rye and lichen had the lowest total phenolic concentrations (1.3 and 1.9% DM) of forages examined, and had lower ADDM's (35 and 40% DM), DE contents (6-7 KJ/g DM), and crude protein (7.8 and 5.7% DM) than seaweeds. The relatively high DE and protein contents of seaweed may explain high deer densities of Maine coastal islands where browse availability and use appears to be low.